2020
DOI: 10.3390/foods9050629
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Chemical Contaminant Levels in Five Marine Fish Species from Angola—The EAF-Nansen Programme

Abstract: Fish is a rich source of several important nutrients and an important part of the otherwise plant-dominated diet present in Angola. However, fish may also be a source of contaminants. The aim of this study was to analyse the nutrient contents and the levels of chemical contaminants, including arsenic, cadmium, mercury, and lead, in five commonly consumed marine fish species sampled during a survey with the research vessel Dr. Fridtjof Nansen in Angola. The species’ contribution to recommended nutrient intakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
4
3
0
Order By: Relevance
“…Among the sampled species, Potassium concentrations ranged between 242 and 410 mg/100 g. The results agree with findings by Nordhagen et al (2020) whose K concentration in fish ranged between 177 and 513 mg/100 g. Findings by Reksten et al (2020a) on Potassium content in fish were within the same range. K concentration in the four selected species was significantly higher in the SEM season compared to NEM season.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among the sampled species, Potassium concentrations ranged between 242 and 410 mg/100 g. The results agree with findings by Nordhagen et al (2020) whose K concentration in fish ranged between 177 and 513 mg/100 g. Findings by Reksten et al (2020a) on Potassium content in fish were within the same range. K concentration in the four selected species was significantly higher in the SEM season compared to NEM season.…”
Section: Discussionsupporting
confidence: 89%
“…The lowest recorded mineral concentration in fish specimens in this study were I, Fe and Zn. Similar studies by Reksten et al (2020a) and Nordhagen et al (2020) also observed lower concentrations of these three minerals in fish muscles compared to Mg, K, Ca and Na concentrations. Zn concentration ranged between 0.5 and 6.13 mg/100 g which is similar to results reported by Nurnadia et al (2013) and Zaman et al, (2014).…”
Section: Discussionsupporting
confidence: 80%
“…Under the EAF-Nansen program, Reksten et al (2020) [ 75 ] analyzed five marine fish from Angola, including two species of sardine ( Sardinella aurita and Sardinella maderensis ). Comparing the nutritional quality of sardine ( S. fimbriata ) from Bangladesh with those from Angola, results showed they have equal amounts of protein but S. fimbriata was higher in calcium, zinc, iron, iodine, and selenium than both S. aurita and S. maderensis .…”
Section: Discussionmentioning
confidence: 99%
“…The significance of food and nutrition security (FNS) is anchored in the United Nations Sustainable Development Goals (SDGs), specifically SDG 2 "Zero Hunger" and SDG 3 "Good Health and Well-Being" [2]. Fish is a source of many essential nutrients [3][4][5][6][7], and can substantially improve FNS especially in a diet that largely consists of starchy staple foods such as cassava, yam, rice, maize and millet, which is the case in Ghana [8][9][10][11]. Compared with animal source foods, starchy foods contain low amounts of micronutrients, have poorer protein quality and may be a source of phytate which further aggravates the severity of undernutrition by inhibiting the absorption of essential minerals and limiting protein and lipid utilization [12,13].…”
Section: Introductionmentioning
confidence: 99%